Supply Chain Management Of Foam Waste Products At Pt. Putra Medal Sakti - Cantika, Cantika; Ratnamurni, Elis Dwiana (SEAN Institute, 2024)
This research aims to analyze the performance of Supply Chain Management at PT. Putra Medal Sakti with SCOR model tools. The method used in this research is a qualitative approach with descriptive methods. From this research it is concluded that in the evaluation section of supply chain management at PT. Putra Medal Sakti, several flows that occurred at PT. Putra Medal Sakti cannot be fulfilled. Supply chain management is not running as well as it should because there are still discrepancies between implementation and planning. Then to measure supply chain management performance at PT. Putra Medal Sakti using the Supply Chain Operation Reference (SCOR) method. Based on the results of performance measurements using the Supply Chain Operation Reference (SCOR) method, the supply chain condition of PT. Putra Medal Sakti has not run as well as it should. This is shown by the perfect order fulfillment value of 74%, order fulfillment cycle time of 3 days, and cash to cash cycle time of 9 days, which is no better than the benchmark data and has a parity value.